Finger on the Pulse: Pumping Iron into Chickpea - Tan, Grace Z. H.; Das Bhowmik, Sudipta S.; Hoang, Thi M. L.; Karbaschi, Mohammad R.; Johnson, Alexander A. T.; Williams, Brett; Mundree, Sagadevan G. (Frontiers in Plant Science, 2017)
Iron deficiency is a major problem in both developing and developed countries, and much of this can be attributed to insufficient dietary intake. Over the past decades several measures, such as supplementation and food fortification, have helped to alleviate this problem. However, their associated costs limit their accessibility and effectiveness, particularly amongst the financially constrained. A more affordable and sustainable option that can be implemented alongside existing measures is biofortification. To date, much work has been invested into staples like cereals and root crops – this has culminated in the successful generation of high iron-accumulating lines in rice and pearl millet. More recently, pulses have gained attention as targets for biofortification. Being secondary staples rich in protein, they are a nutritional complement to the traditional starchy staples. Despite the relative youth of this interest, considerable advances have already been made concerning the biofortification of pulses. Several studies have been conducted in bean, chickpea, lentil, and pea to assess existing germplasm for high iron-accumulating traits. However little is known about the molecular workings behind these traits, particularly in a leguminous context, and biofortification via genetic modification remains to be attempted. This review examines the current state of the iron biofortification in pulses, particularly chickpea. The challenges concerning biofortification in pulses are also discussed. Specifically, the potential application of transgenic technology is explored, with focus on the genes that have been successfully used in biofortification efforts in rice.